Al-Kulira’s Poetry Works of Nazik al-Malaika: Sociological Literature Analysis - Suryaningsih, Iin; Muhammad, Safira; El Sayyed, Wael Ali (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
In 1947, Egypt experienced a cholera epidemic that killed thousands of people every day for three months. Furthermore, Nazik al-Malaika wrote a poem entitled al-Kulira. The poem describes events and expresses deep sorrow over the spread of cholera. The poem became the first free poetry in Arabic literature. This study describes the sociological theory of Wellek & Werren's to find state point of view of the author, the sociology of literary works, and the sociology of the readers of al-Kulira’s poetry, with descriptive analysis method and objective approach. The results of this study is in terms of socio-cultural background in authorship; Nazik, was born in an environment that loves science and literature. It was concluded that Nazik's thought of composing al-Kulira's poetry was influenced by the cholera epidemic sweeping Egypt then. Nazik's expressions in his poetry, which are filled with sorrow and sadness, are influenced by the large number of Egyptian people who died due to a cholera epidemic.